2023
DOI: 10.1039/d3cc03042c
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for high ethylene polymerization performance using titanium single-site catalysts

Lujain Alrais,
Walid Al Maksoud,
Baraa Werghi
et al.

Abstract: The synthesis of heterogeneous Ti(iv)-based catalysts for ethylene polymerization following surface organometallic chemistry concepts is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…With this approach, for example, strong electrostatic interactions between cationic CPEs and DNA and DNA bases were achieved, allowing the detection of DNA and DNA bases based on the fluorescence quenching of the cationic CPEs [21]. In addition to such a fascinating method to detect DNA and DNA bases, efficient energy transfer from photoexcited cationic polyfluorene, one of the CPEs, to porphyrins demonstrated that the cationic polyfluorene can form electrostatic assembly with small molecules, and in the assembly, it acts as a photosensitizer [22].…”
Section: Introductionmentioning
confidence: 99%
“…With this approach, for example, strong electrostatic interactions between cationic CPEs and DNA and DNA bases were achieved, allowing the detection of DNA and DNA bases based on the fluorescence quenching of the cationic CPEs [21]. In addition to such a fascinating method to detect DNA and DNA bases, efficient energy transfer from photoexcited cationic polyfluorene, one of the CPEs, to porphyrins demonstrated that the cationic polyfluorene can form electrostatic assembly with small molecules, and in the assembly, it acts as a photosensitizer [22].…”
Section: Introductionmentioning
confidence: 99%